Relation between endometrial thickness with serum estradiol and progesterone levels in patients visited at Ob&Gyn clinic of Shahid Sadoughi hospital - Robab Davar; Razeah Dehghani Firouzabadi; Kefayat Chaman-Ara (Iranian South Medical Journal, 2015)
Background: The endometrial thickness is an important determinant for the successful implantation and pregnancy. This research was aimed to evaluate relationship between the endometrial thickness with serum estradiol and progesterone levels in patients visited in Ob&Gyn clinic of Shahid Sadoughi hospital.